A distinct chemokine axis does not account for enrichment of Foxp3+ CD4+ T cells in carcinogen‐induced fibrosarcomas. Issue 1 (May 2015) - Ondondo, Beatrice; Colbeck, Emily; Jones, Emma; Smart, Kathryn; Lauder, Sarah N.; Hindley, James; Godkin, Andrew; Moser, Bernhard; Ager, Ann; Gallimore, Awen
Summary The frequency of CD4+ Foxp3+ regulatory T (Treg) cells is often significantly increased in the blood of tumour‐bearing mice and people with cancer. Moreover, Treg cell frequencies are often higher in tumours compared with blood and lymphoid organs. We wished to determine whether certain chemokines expressed within the tumour mass selectively recruit Treg cells, thereby contributing to their enrichment within the tumour‐infiltrating lymphocyte pool. To achieve this goal, the chemokine profile of carcinogen‐induced fibrosarcomas was determined, and the chemokine receptor expression profiles of both CD4+ Foxp3− and CD4+ Foxp3+ T cells were compared. These analyses revealed that the tumours are characterized by expression of inflammatory chemokines (CCL2, CCL5, CCL7, CCL8, CCL12, CXCL9, CXCL10 and CX3CL1), reflected by an enrichment of activated Foxp3− and Foxp3+ T cells expressing T helper type 1‐associated chemokine receptors. Notably, we found that CXCR3+ T cells were significantly enriched in the tumours although curiously we found no evidence that CXCR3 was required for their recruitment. Instead, CXCR3 marks a population of activated Foxp3− and Foxp3+ T cells, which use multiple and overlapping ligand receptor pairs to guide their migration to tumours. Collectively, these data indicate that enrichment of Foxp3+ cells in tumours characterized by expression of inflammatory chemokines, does not occur via a distinct chemokine axis, thus selective chemokine blockade is unlikely to represent a meaningful therapeutic strategy for preventing Treg cell accumulation in tumours.